2022
DOI: 10.1590/1980-265x-tce-2020-0552
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and Barriers to Drug Therapy: Relationship With the Risk of Falls in Older Adults

Abstract: Objective: to verify the association of adherence and barriers to drug therapy with the risk of falls and the sociodemographic, clinical and economic variables. Method: a cross-sectional study, carried out with 117 aged individuals in a Medical Clinic of Specialties for Older Adults in the Southeast region of the city of São Paulo (SP), from March to November 2019. The following scales were applied: Downton Fall Risk, Morisky-Green Test and Brief Medication Questionnaire. Logistic regression was use to verif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
1
0
2
Order By: Relevance
“…The fact is that using medications incorrectly can lead to several risks. A study carried out in Brazil with older adults showed the highest number of falls found in participants who used analgesics, muscle relaxants and anti-inflammatories 30 . This group requires greater attention in RSM practice, considering possible drug interactions, since they already continually use medications to treat chronic non-communicable diseases, which may lead to a reduction or enhancement of a drug's action.…”
Section: /18mentioning
confidence: 99%
“…The fact is that using medications incorrectly can lead to several risks. A study carried out in Brazil with older adults showed the highest number of falls found in participants who used analgesics, muscle relaxants and anti-inflammatories 30 . This group requires greater attention in RSM practice, considering possible drug interactions, since they already continually use medications to treat chronic non-communicable diseases, which may lead to a reduction or enhancement of a drug's action.…”
Section: /18mentioning
confidence: 99%
“…O fato é que usar medicamentos de forma incorreta pode levar a diversos riscos. Um estudo desenvolvido no Brasil com a população idosa mostrou o maior número de quedas encontrado nos participantes que faziam uso de analgésicos, relaxantes musculares e anti-inflamatórios 30 . Este grupo requer maior atenção na prática de AR, tendo em vista possíveis interações medicamentosas, uma vez que já fazem uso contínuo de medicamentos para tratamento de doenças crônicas não transmissíveis, podendo levar à redução ou potencialização da ação do fármaco.…”
Section: /18unclassified
“…Dessa forma, com o aumento na prevalência das DCNT em idosos a associação de vários medicamentos é um fato natural, uma vez que torna-se necessário para o controle dessas doenças. Esse fato é observado pois o acompanhamento da pessoa idosa em muitos casos são realizados por múltiplos especialistas em saúde, que na maioria das vezes não possuem ligação profissional entre si, o que pode gerar à uma possível polifarmácia em cuja definição traz a utilização de 5 ou mais medicamentos por uma só pessoa (Soares, 2022).…”
Section: Introductionunclassified